Structural optimization with teaching-learning-based optimization algorithm - Dede, Tayfun; Ayvaz, Yusuf (TECHNO-PRESS, 2013)
In this paper, a new efficient optimization algorithm called Teaching-Learning-Based Optimization (TLBO) is used for the least weight design of trusses with continuous design variables. The TLBO algorithm is based on the effect of the influence of a teacher on the output of learners in a class. Several truss structures are analyzed to show the efficiency of the TLBO algorithm and the results are compared with those reported in the literature. It is concluded that the TLBO algorithm presented in this study can be effectively used in the weight minimization of truss structures.
Keywords: teaching-learning-based optimization; truss structure; weight minimization; PARAMETER OPTIMIZATION; MULTIOBJECTIVE OPTIMIZATION; DESIGN OPTIMIZATION; OPTIMUM DESIGN; Engineering